Nexus between Key Determinants of Service Quality and Students’ Satisfaction in Higher Education Institutions (HEIs) - Butt, Sadia; Umair, Tahira; Tajammal, Ramshah (Annals of Human and Social Sciences, 2024)
This study examined the nexus between key determinants of SQ and SS in HEIs of Pakistan. This study employed cross-sectional design and quantitative approach. Data was obtained from 235 currently enrolled students in HEIs of Pakistan applying random sampling technique through structured SERVQUAL questionnaire. Data was analyzed through SPSS 23.0 applying statistical analysis. Study findings identified critical service quality dimensions relevant to students’ satisfaction in HEIs. Results of data analysis revealed that five SQ dimensions were positively correlated with student’s satisfaction (SS) in HEIs. While regression analysis results indicated that that only two (2) SQ/SERVQUAL dimensions (Responsiveness and Assurance) had positive significant impact on SS. While, remaining three SERVQUAL dimensions had insignificant impact. Furthermore, the findings are important for policy makers, service providers and management of HEIs for resource allocation decisions and students retention.